O33 Aerobic vaginitis: prevalence, management and outcomes in a large integrated sexual health clinic. (18th May 2015) - Mason, Mark; Little, Bethan; Winter, Andrew
Abstract : Background/introduction: Aerobic vaginitis (AV), a syndrome of abnormal vaginal microflora, was first described in 2002 and is increasingly recognised as a condition distinct from bacterial vaginosis that may require different management. Aim(s)/objectives: To describe the prevalence of moderate-to-severe AV, its management and outcomes in a UK setting. Methods: We included all women presenting to our large integrated sexual health service who met criteria for gynaecological examination and near-patient microscopy. A single biomedical scientist scored the wet mount according to the method of Donders et al . If the score was 5 or above (indicating moderate to severe AV) the requesting clinician was informed. We reviewed case notes to determine treatment choice and outcome. Results: From 1/12/13 to 30/11/14, 1616 wet films were read. Overall, 314 (19.4%) had an abnormal AV score (11 (0.7%) severe AV (score >6), 61 (3.8%) moderate AV (score = 5–6), 253 (15.7%) slight AV (score = 3–4)). Patients with severe AV were significantly older than those with moderate AV (mean age 42.7 vs 32.0 years, p = 0.04), but only 6 (8.3%) patients had atrophic change. Among patients with AV scores of 5 or more, trichomonas was seen in 2 (2.8%) patients, 13 (18.5%) had evidence of yeast infection. First-line treatment included intravaginal clindamycin (49.7%), oral metronidazole (27.3%), antifungals, penicillins, acidification gel and local oestrogen. Symptoms persisted in 19.4%, re-occured in 4.2% and resolved in 43%, with 33% not re-attending. Discussion/conclusion: Patients with moderate-to-severe AV scores are challenging to manage with a high proportion of repeat attendance. Severe AV occurs in an older population.